Advances in Hydrometallurgy - Chagnes, Alexandre (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The development of new technologies and the increasing demand for mineral resources from emerging countries are responsible for significant tensions in the pricing of non-ferrous metals. Some metals have become strategic and critical because they are used in many technological applications such as flat panel TVs (indium), solar panel cells (indium), lithium-ion batteries for electric vehicles (lithium, cobalt), magnets (rare earth elements, such as neodymium and dysprosium), scintillators (rare earths), and aviation and medical applications (titanium); their availabilities remain limited. The secured supply of these metals is crucial to continue producing and exporting these technologies, and because the specific properties of these metals make them essential and difficult to substitute for a given industrial application. Hydrometallurgy have the advantages of being able to process low-grade ores, to allow better control of co-products, and have a lower environmental impact providing that the hydrometallurgical route is optimized and cheap. The need to develop sustainable, efficient, and cheap processes to extract metals from complex and poor polymetallic matrices is real. The aim of this book was to highlight recent advances related to hydrometallurgy to face new challenges in metal production.